Kajian Ekperimen Pengaruh Pemasangan Silinder Sirkular Bervariasi Diameter dengan Posisi X/D = 0.5 dan Y/D = 0.7 pada Sisi Advancing Blade Terhadap Performa Turbin Air Savonius - Difa Falahudin; Priyo Agus Setiawan; Arie Indartono (Politeknik Perkapalan Negeri Surabaya, 2020)
Savonius water turbine has the opportunity to be developed. An innovation is needed toimprove the performance of savonius water turbines. An experimental study on the effect of installing acircular cylinder with varying diameters on the advancing blade side of the savonius water turbineperformance needs to be carried out. The experiment used savonius water turbine myring n = 1 andmyring n = 2 with a diameter and rotor height of 40 cm each. Circular cylinder diameter variations usedare ds/D=0.2, ds/D=0.3, and ds/D=0.4. Circular cylinder is positioned at a distance of X/D=0.5 andY/D=0.7. The result is the coefficient of torque (Ct) and the coefficient of power (Cp). In addition, thediameter of the circular cylinder that is capable of producing the best performance of Savonius waterturbines will be obtained. The results of the experiment indicate that the installation of a circular cylinderon the advancing blade can improve the performance of savonius water turbines. Variation in circularcylinder diameter ds/D=0.4 results the highest Ct and Cp values in the savonius water turbine myringn=1 and myring n=2. Myring n=1 turbine experiment shows the value of Ct obtained is 0.34 at the tipspeed ratio (TSR) of 0.73, while in myring n=2 turbine, the value of Ct obtained is 0.34 at TSR 0.49.Myring n=1 turbine experiment shows a Cp value of 0.25 at TSR 0.73 (showing an increase of 66.67%),whereas in myring n=2 turbine, the Cp value obtained is 0.16 at TSR 0.49 (showing an increase of21.43%).